DETERMINAN KEPUTUSAN INVESTASI EMAS GENERASI Z DI SOLO RAYA - Era Trianita Saputra; Astuning Saharsini; Nanda Fatmawati (JURNAL ILMIAH EDUNOMIKA, 2026)
Investment has become an important financial planning strategy for Generation Z amid economic uncertainty and rapid technological development. This study aims to examine the influence of financial literacy, income, technological advancement, and investment motivation on gold investment decisions among Generation Z in Solo Raya. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 Generation Z respondents who had experience investing in financial instruments such as gold, stocks, mutual funds, cryptocurrencies, or deposits. The sampling technique used was purposive sampling, and the data were analyzed using multiple linear regression with SPSS version 24. The results indicate that financial literacy and technological advancement have a significant negative effect on gold investment decisions, while income and investment motivation have a significant positive effect. Furthermore, the coefficient of determination shows that these variables explain 37.8% of the variation in gold investment decisions. The findings suggest that economic capacity and investment motivation play important roles in encouraging investment behavior, whereas higher financial literacy and technological advancement may lead Generation Z to be more selective and cautious in choosing gold as an investment instrument.